Unknown Extra-Articular Manifestation of Spondyloarthritis: What About Retroperitoneal Fibrosis? A Case Based Literature Review - Boussaid, Soumaya; Majdouba, Marouene B.; Rekik, Sonia; Jammali, Samia; Cheour, Elhem; Sahli, Hela; Elleuch, Mohamed (Current Rheumatology Reviews, 2022)
Introduction: Retroperitoneal fibrosis (RPF) is a rare disease characterized by fibroinflammatory tissue proliferation in the retroperitoneum. It results in a chronic inflammatory and fibrosis condition, possibly leading to compression of the retroperitoneal structures, especially to encasement of the ureters and the inferior vena cava. It may have an idiopathic or a secondary origin. Spondyloarthritis (SpA) is one of the rare conditions described among the secondary forms. Case Presentation: Herein, we report a new case of RPF in a patient with AS presented with acute abdominal pain radiating to the lumbar region and the left testicle. On clinical examination, we found a mild stiffness of the lumbar spine and a decrease in chest expansion. Sacroiliac joint pain was also found. The rest of the physical examination was normal. Laboratory tests showed inflammation with increased C-reactive protein (130 mg/l) and creatinine (112 micromol/l) levels. The computed tomography scan revealed a soft tissue density mass located around the sub-renal aorta. Diagnosis of idiopathic RPF associated with AS was retained. The patient was treated with a daily dosage of 1 mg/kg of oral glucocorticoid with a good outcome. Conclusion: RPF is a rare condition that can be either idiopathic or secondary. Its association with spondyloarthritis, mainly in its ankylosing spondylitis form, seems to be more than anectodal. Treatment may involve medical therapy and/or surgical management. Key Message: In the presence of back pain, fatigue, weight loss, and low grade fever in spondyloarthritis patients, physicians should screen for retroperitoneal fibrosis as it could be a possible cause.
Keywords: Retroperitoneal fibrosis